Method for preparing cyclic carbonate through cycloaddition of CO2 and epoxide and application of cyclic carbonate
By optimizing the ratio of ligands and metal salts and heat treatment conditions of MOF material synthesis, the acidic and alkaline sites on the surface of MOF material are improved, and the problem of easy destruction of the material structure in traditional methods is solved, and efficient CO2 chemical fixation and cycloaddition reaction are achieved.
Patent Information
- Application Number
- CN202411917315.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-24
AI Technical Summary
Prior art In the synthesis of zirconium-based MOF materials, additional steps are required to remove the template, resulting in the destruction of the interposer structure of the material and affecting the catalytic performance.
By formulating a first mixed solution containing a neutral ligand, a hydrogen bond acceptor and a hydrogen bond donor, and a second mixed solution containing a metal salt and a linker, a MOF material is obtained in combination with heat treatment, which significantly improves the acidic and basic sites on the surface of the material and enhances the catalytic performance.
This method significantly improves the cycloaddition reaction efficiency of CO2 and epoxide, with yields reaching 97% and 54%, and achieves chemical fixation of CO2 under relatively mild temperature and pressure conditions, which is highly efficient and economical.
Smart Images

Figure CN119798205A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of greenhouse gas control, and in particular to a method for preparing cyclic carbonate by cycloaddition of CO2 and epoxide and its application. Background Art
[0002] Carbon dioxide (CO2) is the main component of greenhouse gases and is generally considered to be a key factor affecting global climate change. Although CO2 emission control has received considerable attention in the past few decades, anthropogenic CO2 emissions caused by fossil fuel combustion are higher than ever before in order to meet the energy needs of industrial development, economic growth and daily life. Among the technologies for reducing CO2 emissions, carbon capture and storage (CCS) technology is currently being studied more and is generally considered to be an effective method for CO2 emission reduction. Among CCS technologies, post-combustion carbon capture technology is widely used because it can be applied in existing plants by adding process units compared to pre-combustion and in-combustion carbon capture technologies. At present, post-combustion carbon capture technology mainly involves physical and chemical adsorption of CO2 in flue gas, such as wet scrubbing with amine aqueous solution. Converting the captured CO2 into high-value-added products is another solution to reduce CO2 emissions, such as synthesizing CO2 into cyclic carbonates, dimethyl carbonate and cyclic urea through chemical fixation.
[0003] The CO2 cycloaddition method is currently a common method for chemical fixation of CO2. It is mainly based on the acid-base catalysis theory and the solid surface property theory. CO2 reacts with different epoxides in the presence of a catalyst to generate cyclic carbonates. In recent years, metal organic frameworks (MOFs) and their composites, as a heterogeneous mesoporous catalytic material, have shown catalytic properties that convert CO2 into other chemical substances more efficiently than other solid catalysts due to the acidic and basic sites on their surfaces. MOFs materials are coordination polymers self-assembled from multi-dentate organic ligands containing oxygen, nitrogen, etc. (mostly aromatic polyacids and polybases) and transition metal ions. They have many characteristics such as porosity, large specific surface area, multi-metal sites, and acid-base catalytic properties. In particular, zirconium-based MOF materials have been widely used in actual production and life because of their excellent hydrophilicity and excellent chemical thermal stability in acidic and alkaline environments. In addition, the symmetric characteristics of zirconium-based MOF materials enable them to coordinate with various linkers and can be designed into a variety of topological structures, making them heterogeneous catalysts in the process of CO2 chemical fixation. Currently, the commonly used methods for synthesizing this type of MOF materials include solvent evaporation diffusion, microwave-assisted synthesis, ionic liquid / supercritical CO2 emulsion method, metal-ligand-fragment co-assembly method, etc. However, these methods require additional steps to remove the template, which will lead to the destruction of the mesoporous structure in the material. At the same time, its acidic and basic sites will also be reduced, which will affect the catalytic performance of the MOF material. Summary of the invention
[0004] The present invention aims to solve one of the technical problems in the related art to at least some extent. To this end, the present invention provides a method and application of preparing cyclic carbonate by cycloaddition of CO2 and epoxide. The method defines a MOF material and uses it as a catalyst for preparing cyclic carbonate by cycloaddition of CO2 and epoxide, which can significantly improve the conversion efficiency of the reactants.
[0005] To this end, the first aspect of the present invention provides a method for preparing cyclic carbonate by cycloaddition of CO2 and epoxide, the method comprising: contacting epoxide and CO2 under the catalysis of MOF material;
[0006] The MOF material is obtained by the following method: preparing a first mixed solution containing a neutral ligand, a hydrogen bond acceptor and a hydrogen bond donor;
[0007] preparing a second mixed solution containing a metal salt and a linker;
[0008] The second mixed solution is mixed with a regulator and the first mixed solution, and subjected to heat treatment to obtain the MOF material;
[0009] The regulator includes at least one of a carboxylic acid and a carboxylate.
[0010] The present invention synthesizes MOF materials based on the first mixed solution, which can increase the acidic sites and basic sites on the surface of the synthesized MOF materials. Compared with the MOF materials synthesized by the traditional method, the MOF materials synthesized by the present invention present two different acidic sites, weak acidity and strong acidity, while the catalysts of this type synthesized by the traditional method have only one strong acidic site. The change of the basic site is the same as the acidic site, that is, there are more basic sites on the surface of the MOF material synthesized by the present invention, so it can be used as an effective catalyst for the CO2 cycloaddition reaction, and different types of acid-base sites on its surface can more easily catalyze the cycloaddition process of CO2. For example, it shows excellent catalytic activity in the CO2 cycloaddition reaction with epichlorohydrin and styrene oxide, and its yield reaches 97% and 54% respectively. At the same time, the MOF material used in the present invention has a higher diffusion rate for gas adsorption-desorption, so it is more conducive to its CO2 cycloaddition reaction with different types and quantities of epoxides in different temperature ranges, so as to achieve chemical fixation of CO2 with higher efficiency and convert it into high value-added products. In addition, the CO2 fixation method provided by the present invention can chemically fix CO2 under relatively mild temperature and pressure conditions, completely without solvent and without using any external co-catalyst, which also reflects the superiority of this method.
[0011] According to an embodiment of the present invention, the neutral ligand includes one of magnesium nitrate hexahydrate, zinc nitrate hexahydrate, copper nitrate hexahydrate, and cobalt nitrate hexahydrate.
[0012] According to an embodiment of the present invention, the hydrogen bond acceptor includes one of choline chloride, glycine, choline fluoride, acetylcholine chloride, and choline nitrate.
[0013] According to an embodiment of the present invention, the hydrogen bond donor includes one of urea, malic acid, oxalic acid, tartaric acid, benzoic acid, imidazole, and lactic acid.
[0014] According to an embodiment of the present invention, the molar ratio of the neutral ligand, the hydrogen bond acceptor and the hydrogen bond donor is 1:2:1.
[0015] According to an embodiment of the present invention, the metal salt includes at least one of zirconium chloride, zinc nitrate, cupric acetate and ferric chloride.
[0016] According to an embodiment of the present invention, the linking agent includes at least one of phthalic acid, 2-methylimidazole, 2,5-dihydroxyterephthalic acid, and tricarboxylic acid.
[0017] According to an embodiment of the present invention, the mass ratio of the metal salt to the connector is (1-2):(0.5-0.8).
[0018] According to an embodiment of the present invention, the first mixed solution, the regulator and the second mixed solution are mixed in a volume ratio of (1-5):(1-10):(50-100).
[0019] According to an embodiment of the present invention, the temperature of the heat treatment is 120-140°C.
[0020] According to an embodiment of the present invention, the heat treatment time is 18-24 hours.
[0021] According to an embodiment of the present invention, the contacting is performed at 1.5-2 MPa.
[0022] According to an embodiment of the present invention, the contacting is performed at 80-220°C.
[0023] The second aspect of the present invention provides an application of a MOF material in the preparation of a cyclic carbonate by cycloaddition of CO2 and epoxide, comprising: contacting epoxide and CO2 under the catalytic action of the MOF material;
[0024] The MOF material is obtained by the following method: preparing a first mixed solution containing a neutral ligand, a hydrogen bond acceptor and a hydrogen bond donor;
[0025] preparing a second mixed solution containing a metal salt and a linker;
[0026] The second mixed solution is mixed with a regulator and the first mixed solution, and subjected to heat treatment to obtain the MOF material;
[0027] The regulator includes at least one of a carboxylic acid and a carboxylate.
[0028] The present invention synthesizes MOF materials based on the first mixed solution, which can increase the acidic sites and basic sites on the surface of the synthesized MOF material, thereby being used as an effective catalyst for the CO2 cycloaddition reaction, and different types of acid-base sites on its surface can more easily catalyze the CO2 cycloaddition process. At the same time, the MOF material used in the present invention has a high diffusion rate for gas adsorption-desorption, and is therefore more conducive to the CO2 cycloaddition reaction with different types and quantities of epoxides within different temperature ranges, thereby achieving chemical fixation of CO2 with higher efficiency and converting it into high value-added products. In addition, the application can realize the CO2 cycloaddition reaction under relatively mild temperature and pressure conditions, in the absence of any solvent and without the use of any external co-catalyst, which has certain advantages.
[0029] According to an embodiment of the present invention, the neutral ligand includes one of magnesium nitrate hexahydrate, zinc nitrate hexahydrate, copper nitrate hexahydrate, and cobalt nitrate hexahydrate.
[0030] According to an embodiment of the present invention, the hydrogen bond acceptor includes one of choline chloride, glycine, choline fluoride, acetylcholine chloride, and choline nitrate.
[0031] According to an embodiment of the present invention, the hydrogen bond donor includes one of urea, malic acid, oxalic acid, tartaric acid, benzoic acid, imidazole, and lactic acid.
[0032] According to an embodiment of the present invention, the molar ratio of the neutral ligand, the hydrogen bond acceptor and the hydrogen bond donor is 1:2:1.
[0033] According to an embodiment of the present invention, the metal salt includes at least one of zirconium chloride, zinc nitrate, cupric acetate and ferric chloride.
[0034] According to an embodiment of the present invention, the linking agent includes at least one of phthalic acid, 2-methylimidazole, 2,5-dihydroxyterephthalic acid, and tricarboxylic acid.
[0035] According to an embodiment of the present invention, the mass ratio of the metal salt to the connector is (1-2):(0.5-0.8).
[0036] According to an embodiment of the present invention, the first mixed solution, the regulator and the second mixed solution are mixed in a volume ratio of (1-5):(1-10):(50-100).
[0037] According to an embodiment of the present invention, the temperature of the heat treatment is 120-140°C.
[0038] According to an embodiment of the present invention, the heat treatment time is 18-24 hours.
[0039] According to an embodiment of the present invention, the contacting is performed at 1.5-2 MPa.
[0040] According to an embodiment of the present invention, the contacting is performed at 80-220°C.
[0041] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0043] Figure 1 The NH3-TPD spectra of the MOF material synthesized by adding different volumes of the first mixed solution in Example 1 of the present invention are shown;
[0044] Figure 2 The CO2-TPD spectra of the MOF material synthesized by adding different volumes of the first mixed solution in Example 1 of the present invention are shown;
[0045] Figure 3 The time and TCD signal spectra of the MOF material synthesized by adding different volumes of the first mixed solution in Example 1 of the present invention at 100° C. are shown;
[0046] Figure 4 The cycloaddition reaction of CO2 and epichlorohydrin catalyzed by the UiO-66 material, the functionalized UiO-66-F material, and the relineMgx5@UiO-66 material in Example 2 of the present invention is shown. 1 HNMR spectra. (a) shows the cycloaddition reaction of CO2 and epichlorohydrin catalyzed by UiO-66 material, functionalized UiO-66-F material, and relineMgx5@UiO-66 material. 1 HNMR spectrum comparison; (b) shows relineMg x5 @UiO-66 catalyzed cycloaddition reaction of CO2 and epichlorohydrin 1 HNMR spectrum;
[0047] Figure 5 The results show that the MOF material synthesized by adding different volumes of the first mixed solution in Example 2 of the present invention catalyzes the cycloaddition reaction of CO2 and epichlorohydrin.1 HNMR spectrum;
[0048] Figure 6 The results show that the MOF material synthesized by adding different volumes of the first mixed solution in Example 3 of the present invention and the UiO-66 material synthesized by the traditional method catalyze the cycloaddition reaction of CO2 and styrene oxide. 1 HNMR spectrum. DETAILED DESCRIPTION
[0049] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be understood as limiting the present invention.
[0050] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of the present invention, unless otherwise specified, the meaning of "plurality" is two or more.
[0051] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0052] In order to make the present invention more easily understood, certain technical and scientific terms are specifically defined below. Unless otherwise clearly defined elsewhere in this document, all other technical and scientific terms used herein have the meanings commonly understood by those skilled in the art to which the present invention belongs.
[0053] In this document, the terms “include” or “comprising” are open expressions, that is, including the contents specified in the present invention but not excluding other contents.
[0054] As used herein, the terms "optionally", "optional" or "optionally" generally mean that the subsequently described event or circumstance may but need not occur, and that the description includes instances where the event or circumstance occurs and instances where it does not.
[0055] According to an embodiment of the present invention, a first aspect of the present invention provides a method for preparing a cyclic carbonate by cycloaddition of CO2 and epoxide, the method comprising: contacting epoxide and CO2 under the catalysis of a MOF material;
[0056] The MOF material is obtained by the following method: preparing a first mixed solution containing a neutral ligand, a hydrogen bond acceptor and a hydrogen bond donor;
[0057] preparing a second mixed solution containing a metal salt and a linker;
[0058] The second mixed solution is mixed with a regulator and the first mixed solution, and subjected to heat treatment to obtain the MOF material;
[0059] The regulator includes at least one of a carboxylic acid and a carboxylate.
[0060] This method uses a specific method to obtain a MOF material, which has a mesoporous structure and retains additional acidic and basic sites. It can be used as a heterogeneous mesoporous catalyst in the process of chemical fixation of CO2, and can undergo CO2 cycloaddition reaction with epoxides to improve their conversion efficiency into polycarbonates and cyclic carbonates.
[0061] Specifically, compared with the MOF material synthesized by the traditional method, the MOF material obtained by the above method has two sites (acidic sites and basic sites), and the number of the two sites has increased, which makes it easier to catalyze the cycloaddition reaction of CO2. In addition, by exploring the adsorption and desorption rates of gases on the surface of MOF materials, the activation state of the sites in the porous medium can be further determined. After the gas molecules are adsorbed on the surface of the material, they are gradually released as the temperature rises. The MOF material synthesized by the present invention has a higher diffusion rate for the adsorption-desorption process of the gas, so it is more conducive to its CO2 cycloaddition reaction with different types and quantities of epoxides in different temperature ranges, thereby achieving chemical fixation of CO2 with higher efficiency and converting it into high value-added products. At the same time, the method provided by the present invention can achieve chemical fixation of CO2 under relatively mild temperature and pressure conditions, in the absence of any solvent and without any external co-catalyst, which confirms that the catalytic activity of the catalyst used in the present invention is good.
[0062] According to a specific embodiment of the present invention, the contacting is carried out at 1.5-2 MPa and 80-220° C. Thus, a higher yield and a higher conversion rate of epoxide can be achieved.
[0063] According to a specific embodiment of the present invention, the epoxide includes at least one of epichlorohydrin, styrene oxide, propylene oxide, ethylene oxide, epoxycyclohexene, epoxylimonene or epoxyvinylcyclohexene.
[0064] According to a specific embodiment of the present invention, the types of the neutral ligand, hydrogen bond acceptor, and hydrogen bond donor are not particularly limited, and those skilled in the art may select them according to the circumstances. As some specific examples, the neutral ligand includes but is not limited to magnesium nitrate hexahydrate, zinc nitrate hexahydrate, copper nitrate hexahydrate, cobalt nitrate hexahydrate, etc.; the hydrogen bond acceptor includes but is not limited to choline chloride, glycine, choline fluoride, acetylcholine chloride, choline nitrate; the hydrogen bond donor includes but is not limited to urea, malic acid, oxalic acid, tartaric acid, benzoic acid, imidazole, and lactic acid.
[0065] According to a specific embodiment of the present invention, the molar ratio of the neutral ligand, the hydrogen bond acceptor and the hydrogen bond donor is 1:2:1.
[0066] According to a specific embodiment of the present invention, the types of the metal salt and the linker are not particularly limited, and those skilled in the art may select them according to the circumstances. As some specific examples, the metal salt includes but is not limited to zirconium chloride, zinc nitrate, copper acetate, ferric chloride, etc.; the linker includes but is not limited to phthalic acid, 2-methylimidazole, 2,5-dihydroxyterephthalic acid, tricarboxylic acid, etc. Among them, tricarboxylic acid should be understood as an organic acid containing three carboxylic acids in its molecular structure.
[0067] According to a specific embodiment of the present invention, the preparation of the second mixed solution is not particularly limited, and the second mixed solution can be obtained by dissolving the metal salt and the linker in a solvent. The type of the solvent is not particularly limited, including but not limited to dimethylformamide and the like.
[0068] According to a specific embodiment of the present invention, the mass ratio of the metal salt and the connector is (1-2):(0.5-0.8). As some specific examples, the mass ratio of the metal salt and the connector may be 1:0.5, 1:0.8, 1.5:0.5, 1.7:0.8, 2:0.5, 2:0.8, etc.
[0069] According to a specific embodiment of the present invention, the first mixed solution, the regulator and the second mixed solution are mixed in a volume ratio of (1-5):(1-10):(50-100. As some specific examples, the volume ratio of the first mixed solution, the regulator and the second mixed solution is 1:1:50, 1:1:75, 1:5:100, 2:7:75, 3:7:100, 5:10:100, etc.
[0070] According to a specific embodiment of the present invention, the regulator includes at least one of carboxylic acid and carboxylate, as some specific examples, including but not limited to formic acid, formates, propionates, etc. The regulator will generate connection defects on the surface of the MOF material and help the first mixed solution to establish additional connections with the metal nodes.
[0071] According to a specific embodiment of the present invention, the temperature and time of the heat treatment are not particularly limited, and those skilled in the art may select them according to the circumstances. As some specific examples, the temperature of the heat treatment is 120-140°C; the time of the heat treatment is 18-24h.
[0072] According to a specific embodiment of the present invention, the method for preparing the MOF material further includes: mixing the second mixed solution with a regulator and the first mixed solution, and obtaining the MOF material through heat treatment, washing, activation and drying.
[0073] Specifically, the washing method is not particularly limited, and washing can be performed by ethanol or dimethylformamide.
[0074] Specifically, the activation method is not particularly limited, and the sample can be placed in acetone to remove the suspension solvent and activate the product at the same time. Usually after the MOF material synthesis process is completed, some unreacted metal ions and organic linking molecules will remain in its structure. In order to remove the unreacted organic linking molecules, acetone can be used to activate the final MOF product. After activation, it can be washed with methanol and then dried to obtain the MOF material.
[0075] According to an embodiment of the present invention, a second aspect of the present invention provides an application of a MOF material in the preparation of a cyclic carbonate by cycloaddition of CO2 and epoxide, comprising: contacting epoxide and CO2 under the catalytic action of the MOF material;
[0076] The MOF material is obtained by the following method: preparing a first mixed solution containing a neutral ligand, a hydrogen bond acceptor and a hydrogen bond donor;
[0077] preparing a second mixed solution containing a metal salt and a linker;
[0078] The second mixed solution is mixed with a regulator and the first mixed solution, and subjected to heat treatment to obtain the MOF material;
[0079] The regulator includes at least one of a carboxylic acid and a carboxylate.
[0080] The MOF material used in this application is the same as the MOF material used in the aforementioned method. The specific details can be referred to above and will not be repeated here.
[0081] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.
[0082] Example 1
[0083] In this embodiment, different volumes of the first mixed solution are used to synthesize the MOF material, as follows:
[0084] (1) Magnesium nitrate hexahydrate (Mg(NO3)3·6H2O), choline chloride and urea were added to a beaker in a molar ratio of 1:2:1, and placed in an oven preheated to 100°C to allow them to stand until they become liquid. The three liquids were mixed on a magnetic stirrer, and then the solution was heated to a clear and transparent liquid without any bubbles. Thus, a magnesium-based coordination low eutectic solvent (i.e., the first mixed solution) was prepared and named relineMg;
[0085] (2) dissolving 1.06 g of zirconium chloride and 0.67 g of phthalic acid in 50 mL of dimethylformamide at room temperature, and stirring on a magnetic stirrer for 10 min to obtain a second mixed solution;
[0086] (3) adding 5 mL of formic acid to the second mixed solution, stirring for 10 min, and ultrasonically treating for 30 min to ensure that all components are completely and evenly distributed in the solution;
[0087] (4) 1 mL, 2 mL, 3 mL, and 5 mL of relineMg were added dropwise to the mixed solution, stirred on a magnetic stirrer for another 30 min, and ultrasonically treated for 45 min to completely disperse the added components;
[0088] (5) The mixture was placed in a 100 mL Teflon-lined autoclave and heated to 120 °C for 24 h;
[0089] (6) After the reaction is completed, the mixture is washed several times with hot ethanol and then washed several times with hot dimethylformamide solvent;
[0090] (7) The sample was placed in 30 mL of acetone and allowed to stand overnight to remove the suspended solvent and activate the product. After activation, it was washed with methanol three times and dried in vacuum at 80 °C overnight to obtain the heterogeneous mesoporous catalytic material relineMg@UiO-66 synthesized with different concentrations of relineMg.
[0091] The prepared MOF materials were named relineMg x1 @UiO-66, relineMg x2 @UiO-66, relineMg x3 @UiO-66, relineMg x5 @UiO-66, where x1 = 1 mL relineMg, x2 = 2 mL relineMg, and so on.
[0092] In addition, the UiO-66 metal organic framework material (hereinafter referred to as Parent@UiO-66 or Parent UiO-66 or UiO-66 material) was prepared by conventional methods, specifically: 0.67g of phthalic acid and 1.06g of ZrCl4 were dissolved in 50mL of dimethylformamide and 5mL of formic acid. Stir on a magnetic stirrer for 10 minutes and then ultrasonically disperse for 30 minutes. After ultrasonic treatment, the mixture was placed in a 100mL autoclave, heated to 120°C, and kept for 24 hours. After the product was cooled to room temperature, it was washed three times with dimethylformamide. In order to activate the sample and remove unreacted dimethylformamide from its structure, the white solid powder was placed in 30ml of acetone overnight, then washed several times with methanol and dried under vacuum at 80°C.
[0093] Since the acidic and basic sites on the surface of the catalytic material are crucial to the process of chemical fixation of CO2, the five catalytic materials (relineMg x1 @UiO-66, relineMg x2 @UiO-66, relineMg x3 @UiO-66, relineMg x5 The Lewis acid and Bronsted basic sites of Parent@UiO-66 and Parent@UiO-66 were determined by calculating the integrated area of the peaks to obtain the intensity of the acid and base sites, thereby identifying the catalytic activity level of the catalytic material.
[0094] In similar studies, the acid sites are mainly divided into three groups of peaks: weak acid (50-100°C), medium acid (150-200°C), and strong acid (320-500°C). In this embodiment, in order to obtain the peak area by grouping more accurately, the acid sites in the NH3-TPD analysis results are divided into two groups of peaks: weak to medium acid (50-320°C), strong acid (320-400°C), as shown in FIG. Figure 1 As shown in the figure, the peaks in the spectrum indicate that the acid sites in the MOF material are closely related to the concentration of the low eutectic solvent (i.e., the first mixed solution) used. As the temperature increases, the integrated peak area shifts to the right, the peak area becomes larger, and the peak intensity gradually increases with the increase in the amount of the first mixed solution added. The high peak intensity of the catalytic material indicates that the material has more acid sites, which may be due to the presence of Mg on the surface of the porous material. 2+ and Zr 2+ Compared with the UiO-66 metal organic framework material (Parent@UiO-66) synthesized by traditional methods, the relineMg x1 @UiO-66, relineMg x2@UiO-66, relineMg x3 @UiO-66, relineMg x5 @UiO-66 material shows two different TPD peaks of weak acidity and medium acidity in different temperature ranges, while UiO-66 material has only one strong acidity peak. More than one acidic and basic site on the surface of the material can improve the availability of the site, indicating that relineMg x1 @UiO-66, relineMg x2 @UiO-66, relineMg x3 @UiO-66, relineMg x5 @UiO-66 material is more likely to catalyze the cycloaddition process of CO2.
[0095] Figure 2 Corresponding to the CO2-TPD spectrum, different base sites of different intensities are also divided into two groups: weak base (50-177°C) and medium-strong base (177-500°C). The results show that compared with the UiO-66 metal organic framework material synthesized by the traditional method, the relineMg@UiO-66 material in this embodiment has significant alkalinity and significantly higher alkaline sites. At the same time, with the increase in the amount of the first mixed solution added, the CO2-TPD spectrum shows a similar pattern to the NH3-TPD spectrum, and the peak intensity and area increase, indicating that the alkaline sites on its surface are also increasing. The increase in peak intensity and peak area may be due to the increase in nitrogen and oxygen atoms in its structure, resulting in more basic groups and sites in the structure.
[0096] In addition, NH3-TPD analysis can also help determine the rate of gas adsorption-desorption processes in catalytic materials as the experimental temperature increases. The study of the rate of gas adsorption and desorption processes on the surface of MOF materials can help determine the activation state of the porous medium, where the gas molecules are tightly bound to the porous medium and released as the temperature increases. Figure 3 It can be seen that within 60 minutes of the experiment, as the first mixed solution increased (from 1 mL to 5 mL), relineMg x5 @UiO-66 can show the maximum peak within 10 minutes. This shows that relineMg x5 @UiO-66 has the maximum gas diffusion rate and has strong catalytic active sites, which is more conducive to CO2 cycloaddition reaction with different amounts of epoxides in different temperature ranges, thereby converting CO2 into value-added products with higher returns through chemical fixation.
[0097] Example 2
[0098] This embodiment uses relineMg x5@UiO-66 catalyzes the cycloaddition reaction of CO2 and epichlorohydrin as follows:
[0099] (1) A 25 mL stainless steel autoclave device connected to an external temperature controller and a magnetic stirrer was purged with pure CO2 gas (99.99%) 3 to 5 times to remove residual air or other gases in the device;
[0100] (2) Without adding any external solvent and co-catalyst, the UiO-66 material, the functionalized UiO-66-F material, and the relineMgx5@UiO-66 material synthesized in Example 1 were placed in a reaction container, and then 30 mmol of epichlorohydrin was added;
[0101] Among them, the functionalized UiO-66-F material uses formic acid (F) as a regulator to produce more open metal sites or missing connection defects, so that the MOF material reacts more effectively with epoxides. The preparation method is as follows:
[0102] 1.06g ZrCl4 and 0.67g phthalic acid were dissolved in 50mL dimethylformamide, stirred on a magnetic stirrer for 30min, 5mL formic acid was added, stirred for 10min and then ultrasonicated in an ultrasonicator for 30min. After complete dissolution, the mixture was added to a 100ml Teflon-lined autoclave and heated in an oven at 120°C for 24h. Before the mixture was cooled to room temperature, it was washed three times with dimethylformamide and then suspended in 30mL acetone overnight to remove excess dimethylformamide. Subsequently, it was washed with methanol and vacuum dried in a vacuum oven at 80°C overnight to obtain UiO-66-F material;
[0103] (3) The reactor was sealed and pressurized to the target pressure within a fixed time. The gas-solid phases were mixed by an external magnetic stirrer at a speed of 600 rpm and heated to 100 °C with the help of an external heating controller.
[0104] (4) The reaction time lasts for 12 hours. After the experiment is completed, the reaction temperature is cooled to room temperature, the unreacted CO2 gas is slowly discharged, and the mixture is filtered with a filter to obtain the target product after cycloaddition.
[0105] In this example, the catalytic efficiency of the three different catalytic materials in step (2) for the cycloaddition reaction of CO2 and epichlorohydrin at 100°C and 2MPa was first compared. 1 HNMR spectrum Figure 4As shown. DMSO is the NMR solvent used in the NMR test. Compared with other MOF materials, under the catalysis of relineMgx5@UiO-66 material, the product showed a higher intensity peak, while the product peak intensity of the other two MOFs catalytic materials was lower. This shows that the method proposed in the present invention can increase the rate of conversion of CO2 and epichlorohydrin into cyclic carbonates. Table 1 gives the catalytic yield of the product under this embodiment, among which relineMg@UiO-66 has the highest catalytic yield of 97% compared with other MOFs materials, while the catalytic yield of UiO-66 material is the lowest, which is 26%. The results show that the catalyst provided by the present invention exhibits higher catalytic performance in the cycloaddition reaction of CO2 and epichlorohydrin.
[0106] Table 1
[0107]
[0108] Secondly, this example also compares the catalytic performance of the MOF materials synthesized with different addition amounts of the first mixed solution on the cycloaddition reaction of CO2 and epichlorohydrin, such as Figure 5 As shown. Under lower temperature and pressure conditions (100°C, 2MPa), the MOF materials prepared by using different addition amounts of the first mixed solution showed excellent performance in the CO2 cycloaddition reaction with epichlorohydrin, with a high conversion rate. x5 @UiO-66 has a higher intensity peak associated with the product (cyclic carbonate) compared to the material synthesized with low solution addition, indicating that it has the highest conversion rate.
[0109] Finally, this embodiment also tests the relineMg at a constant temperature of 100°C. x5 @UiO-66 was tested for its catalytic performance in the cycloaddition reaction of epichlorohydrin and CO2 under different pressure conditions. x5 @UiO-66 exhibits excellent catalytic activity for the CO2 quantitative cycloaddition reaction of epichlorohydrin. It is also found that the yield of the chemical cycloaddition reaction increases with the increase of applied pressure, as shown in Table 2. x5 @UiO-66 has the highest catalytic yield of 97% at 100°C and 2MPa; at the same constant temperature of 100°C and pressure of 1MPa, the lowest catalytic yield is 64%. The catalytic yield of the catalytic material used in this example is higher than any other MOFs material reported so far. In the absence of a co-catalyst and a completely solvent-free environment, the yield percentage of MOFs materials currently x5 @UiO-66 catalytic material has a very high catalytic activity.
[0110] Table 2
[0111]
[0112] Example 3
[0113] This embodiment uses relineMg x5 @UiO-66 catalyzes the cycloaddition reaction of CO2 and styrene oxide as follows:
[0114] (1) A 25 mL stainless steel autoclave device connected to an external temperature controller and a magnetic stirrer was purged with pure CO2 gas (99.99%) 3 to 5 times to remove residual air or other gases in the device;
[0115] (2) Without adding any external solvent and promoter, UiO-66 material and relineMg synthesized in Example 1 were added. x5 @UiO-66 materials were placed in the reaction container, and then 30mmol of styrene oxide was added;
[0116] (3) The reactor was sealed and pressurized to the target pressure within a fixed time. The gas-solid phases were mixed by an external magnetic stirrer at a speed of 600 rpm and heated to 100 °C with the help of an external heating controller.
[0117] (4) The reaction time lasts for 12 hours. After the experiment is completed, the reaction temperature is cooled to room temperature, the unreacted CO2 gas is slowly discharged, and the mixture is filtered with a filter to obtain the target product after cycloaddition.
[0118] from Figure 6 It can be seen that when the UiO-66 material is used as a catalyst for the CO2 cycloaddition reaction with styrene oxide, almost no target product, namely styrene carbonate, is generated. x5 @UiO-66 as a heterogeneous catalyst, 1 Some small peaks appeared in the HNMR spectrum, which are related to the products of the cycloaddition reaction of CO2 and styrene oxide. Therefore, it can be shown that under the same temperature and pressure conditions, relineMg x5 @UiO-66 has better catalytic performance for styrene oxide than UiO-66 material synthesized by traditional methods. In this embodiment, different pressures are also applied to the reaction vessel to observe the changes in the catalytic performance of the material. As the pressure conditions increase, the yield also shows an increasing trend. Under the conditions of temperature 100°C and pressure 2MPa, the catalytic yield of the cycloaddition reaction of styrene oxide and CO2 can reach up to 54%, as shown in Table 3.
[0119] Table 3
[0120]
[0121] These results indicate that the method for chemically fixing CO2 by catalyzing cycloaddition reaction of MOF materials provided in the present invention can carry out CO2 cycloaddition reaction with different epoxides under relatively mild temperature and pressure conditions to chemically fix CO2 into products with high added value, such as polycarbonates and cyclic carbonates.
[0122] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0123] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing cyclic carbonate by cycloaddition of CO2 and epoxide, characterized in that: The method comprises: contacting epoxide and CO2 under the catalysis of MOF material; The MOF material is obtained by the following method: preparing a first mixed solution containing a neutral ligand, a hydrogen bond acceptor and a hydrogen bond donor; preparing a second mixed solution containing a metal salt and a linker; The second mixed solution is mixed with a regulator and the first mixed solution, and subjected to heat treatment to obtain the MOF material; The regulator includes at least one of a carboxylic acid and a carboxylate.
2. The method according to claim 1, characterized in that The neutral ligand includes one of magnesium nitrate hexahydrate, zinc nitrate hexahydrate, copper nitrate hexahydrate, and cobalt nitrate hexahydrate; Optionally, the hydrogen bond acceptor comprises one of choline chloride, glycine, choline fluoride, acetylcholine chloride, and choline nitrate; Optionally, the hydrogen bond donor includes one of urea, malic acid, oxalic acid, tartaric acid, benzoic acid, imidazole, and lactic acid; Optionally, the molar ratio of the neutral ligand, the hydrogen bond acceptor and the hydrogen bond donor is 1:2:
1.
3. The method according to claim 1, characterized in that: The metal salt includes at least one of zirconium chloride, zinc nitrate, copper acetate, and ferric chloride; Optionally, the linking agent includes at least one of phthalic acid, 2-methylimidazole, 2,5-dihydroxyterephthalic acid, and tricarboxylic acid.
4. The method according to claim 1, characterized in that: The mass ratio of the metal salt to the linker is (1-2):(0.5-0.8); Optionally, the first mixed solution, the regulator and the second mixed solution are mixed in a volume ratio of (1-5):(1-10):(50-100).
5. The method according to claim 1, characterized in that The temperature of the heat treatment is 120-140°C; Optionally, the heat treatment time is 18-24h; Optionally, the contacting is carried out at 1.5-2 MPa; Optionally, the contacting is carried out at 80-220°C.
6. Application of a MOF material in the preparation of cyclic carbonate by cycloaddition of CO2 and epoxide, characterized in that: include: contacting epoxide and CO2 under the catalysis of the MOF material; The MOF material is obtained by the following method: preparing a first mixed solution containing a neutral ligand, a hydrogen bond acceptor and a hydrogen bond donor; preparing a second mixed solution containing a metal salt and a linker; The second mixed solution is mixed with a regulator and the first mixed solution, and subjected to heat treatment to obtain the MOF material; The regulator includes at least one of a carboxylic acid and a carboxylate.
7. The use according to claim 6, characterized in that: The neutral ligand includes one of magnesium nitrate hexahydrate, zinc nitrate hexahydrate, copper nitrate hexahydrate, and cobalt nitrate hexahydrate; Optionally, the hydrogen bond acceptor comprises one of choline chloride, glycine, choline fluoride, acetylcholine chloride, and choline nitrate; Optionally, the hydrogen bond donor includes one of urea, malic acid, oxalic acid, tartaric acid, benzoic acid, imidazole, and lactic acid; Optionally, the molar ratio of the neutral ligand, the hydrogen bond acceptor and the hydrogen bond donor is 1:2:
1.
8. The use according to claim 6, characterized in that: The metal salt includes at least one of zirconium chloride, zinc nitrate, copper acetate, and ferric chloride; Optionally, the linking agent includes at least one of phthalic acid, 2-methylimidazole, 2,5-dihydroxyterephthalic acid, and tricarboxylic acid.
9. The use according to claim 6, characterized in that: The mass ratio of the metal salt to the linker is (1-2):(0.5-0.8); Optionally, the first mixed solution, the regulator and the second mixed solution are mixed in a volume ratio of (1-5):(1-10):(50-100).
10. The use according to claim 6, characterized in that: The temperature of the heat treatment is 120-140°C; Optionally, the heat treatment time is 18-24h; Optionally, the contacting is carried out at 1.5-2 MPa; Optionally, the contacting is carried out at 80-220°C.
Citation Information
Patent Citations
CN (at) ZrO2 composite material and application thereof in catalysis of cycloaddition reaction of CO2 and epoxide
CN114939431A
Ionic metal-organic framework catalyst for CO2 cycloaddition reaction as well as preparation method and application of ionic metal-organic framework catalyst
CN116571280A